Diabetes Pada Anak - Yulisnawati Hasanah (Conferences of Medical Sciences Dies Natalis, 2019)
Diabetes mellitus (DM) is a complex metabolic disorder characterized by the condition of persistent hyperglycemia due to abnormalities in insulin secretion, insulin action, or both. DM type 1 is more often often found in children but with increasing obesity rates, the number of children with type 2 diabetes is increasing. In children who have been diagnosed, determining the type of DM becomes important because of its large clinical implications especially for the choice of therapy. The determination of the type of DM is based on the clinical characteristics of the patient, but differentiating the various types is not always easy and is still a challenge in itself. DM management aims to achieve controlled glucose levels and prevent complications, both acute or chronic complications. Complications related to metabolic control and duration of suffering from DM, so early detection of DM especially in high-risk children should be sought as part of the prevention of DM and its various complications.